Snap Bean (Phaseolus vulgaris) Response to Deficit Irrigation and Nitrogen Fertilizer and Relationships between Yield, Yield Component, and Protein Content - Melaku Fisseha Teferi; Bizuayehu Tesfaye; Abraham Woldemichael; Adugna Debella (International Journal of Agronomy)
Field experiments were conducted at Adami Tulu, Ethiopia, for two successive dry seasons to investigate how nitrogen levels and deficit irrigation affect the yield and its related components, and the protein content of snap beans. The treatments were deficit irrigation with three levels (50, 75, and 100% ETc) and application of nitrogen with four levels (0, 46, 92, and 138 kg·N·ha−1), which were set up as split-plot arrangement, with irrigation being as the main plot and nitrogen levels as subplot, replicated thrice. Results showed that the pod yield had a substantial impact (p<0.01) on the interaction between the two factors; i.e., interaction of 100% ETc and 92 kg nitrogen levels per hectare recorded the highest pod yield (22.69 t·ha−1), but treatment combinations of 50% ETc and no nitrogen application produced the lowest amount of overall pod yield (6.922 tons per hectare). However, the results showed that the application of 75% ETc in combination with 92 kg nitrogen per hectare recorded the highest protein concentration (17.718%) but statistically equivalent to 138 kg nitrogen per hectare combined with the same deficit irrigation level, while the lowest protein concentration (12.24%) was recorded at 50 ETc combined with no fertilizer. Hence, the use of 75% ETc along with 92 kg nitrogen levels per hectare could be optimal in balancing quality and pod output of green beans at Adami Tulu and surrounding areas.